Effect of Dynamic Wind Load on Tall Structure Using Gust Factor Method - MALI, AMIT K; Patel, Vishalkumar B.; Desai, Atul N. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
With advancements in construction materials and design technologies, as well as the context of substantial urban growth, tall structures are increasing day by day, and the cost of land is also rising. Hence, constructing tall structures is the best way to expand vertically. In this study, shear force and bending moment multipliers were calculated using MATLAB for 155,040 data samples. The main objective of the paper was to investigate the effect of the gust factor on a 100m tall structure, while keeping the B/H ratio between 0.2 and 1.2 and the L/B ratio of the building varying from 0 to 50. The height of the structure was varied from 50m to 450m to analyze the shear force and bending moment multipliers. Furthermore, the study aimed to examine the effect of the fundamental frequency of the building structure on the gust factor and to prepare elastic spectra accordingly. As the slenderness ratio increases, the gust factor also increases. The gust factor for flexible structures was higher than that for stiff buildings. The elastic spectra revealed that with an increase in frequency, the gust factor decreases, and at a certain frequency value, it becomes constant. The current study utilized shear force and bending moment multipliers, as well as the elastic spectra of gust, to calculate shear force and bending moment. This method proved to be quicker than manual calculations. The shear force and bending moment obtained from the present study were compared to those from IS 875:2015, and the error was found to be smaller than 10%.